2017
DOI: 10.1007/s13402-017-0363-3
|View full text |Cite
|
Sign up to set email alerts
|

Amphiregulin regulates proliferation and migration of HER2-positive breast cancer cells

Abstract: Based on our results we conclude that AREG is involved in regulating the proliferation and migration of erbB2/HER2-positive breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Skin diseases, such as psoriasis, can be triggered by physical injury in susceptible patients (known as the Koebner phenomenon), and it is critical to understand the elements participating in processes occurring in cutaneous wounds (44,45). Additionally, it has been suggested that endogenous AREG modulates tissue repair and regulates the migration of several cell types, such as breast cancer cells (46,47). The current findings confirmed that NMD perturbation in keratinocytes promoted wound re-epithelialization by adjusting endogenous AREG levels.…”
Section: Discussionsupporting
confidence: 77%
“…Skin diseases, such as psoriasis, can be triggered by physical injury in susceptible patients (known as the Koebner phenomenon), and it is critical to understand the elements participating in processes occurring in cutaneous wounds (44,45). Additionally, it has been suggested that endogenous AREG modulates tissue repair and regulates the migration of several cell types, such as breast cancer cells (46,47). The current findings confirmed that NMD perturbation in keratinocytes promoted wound re-epithelialization by adjusting endogenous AREG levels.…”
Section: Discussionsupporting
confidence: 77%
“…Cell invasion and migration are important processes in breast cancer development and metastasis and have become a challenging problem in clinical treatment 40. The Transwell assays suggested that treatment with higher doses of nanocomposites can significantly reduce the number of invaded cells, and the effects showed a dose dependent (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…This data suggests that ILC2s could be activated by IL-33 to secrete IL-5 and IL-13 in the 4T1 model of breast cancer, but further investigation is required to confirm this finding also in patients. Moreover, it has been shown that AREG regulates the proliferation and the migration of different mouse and human estrogen-receptor positive (ER2 + ) breast cancer cell lines (87). However, it is still unknown whether ILC2s and ILC2-derived AREG are involved in this pro-tumoral axis.…”
Section: Ilc2s In Breast Cancermentioning
confidence: 99%